18S rDNA Phylogeny of Lamproderma and Allied Genera (Stemonitales, Myxomycetes, Amoebozoa) - Fiore-Donno, Anna Maria; Kamono, Akiko; Meyer, Marianne; Schnittler, Martin; Fukui, Manabu; Cavalier-Smith, Thomas (PLOS ONE, 2012)
The phylogenetic position of the slime-mould genus Lamproderma (Myxomycetes, Amoebozoa) challenges traditional taxonomy: although it displays the typical characters of the order Stemonitales, it appears to be sister to Physarales. This study provides a small subunit (18S or SSU) ribosomal RNA gene-based phylogeny of Lamproderma and its allies, with new sequences from 49 specimens in 12 genera. We found that the order Stemonitales and Lamproderma were both ancestral to Physarales and that Lamproderma constitutes several clades intermingled with species of Diacheopsis, Colloderma and Elaeomyxa. We suggest that these genera may have evolved from Lamproderma by multiple losses of fruiting body stalks and that many taxonomic revisions are needed. We found such high genetic diversity within three Lamproderma species that they probably consist of clusters of sibling species. We discuss the contrasts between genetic and morphological divergence and implications for the morphospecies concept, highlighting the phylogenetically most reliable morphological characters and pointing to others that have been overestimated. In addition, we showed that the first part (∼600 bases) of the SSU rDNA gene is a valuable tool for phylogeny in Myxomycetes, since it displayed sufficient variability to distinguish closely related taxa and never failed to cluster together specimens considered of the same species.